Effect of Different Soaking Pre-treatments on Quality of Potato Chips Granola Variety (Solanum tuberosum L.) - Rifah Arum; Wanti Dewayani; Erina Septianti; Riswita Syamsuri; Suryani Suryani (Universitas Panji Sakti, 2022)
Potato chips are one of the snacks flavored by the public. This study aimed to determine the effect of soaking pre-treatment on the quality of Granola potato chips. The research was conducted at the Postharvest Laboratory of BPTP South Sulawesi from June to December 2017. The experimental design of RAL was carried out with 3 replications with 6 immersion treatments, namely in plain water, 0.5% Ca(OH)2 solution, 1% Ca(OH)2, Na2S2O5 0.5%, 1% Na2S2O5, 0.5% CaCl2 and 1% CaCl2. The results showed that the chemical and organoleptic characteristics were significantly different between all treatments. The best or the most preferred treatment by the panelists was potato chips soaked in 1% CaCl2 solution with a yield of 20.47%; moisture content 3.80%, 11.79% fiber, 34.79% fat, 30.24% starch, 2.5% ash, and the level of color preference (score 4.80), aroma (score 5.00), texture (score 4.60) and overall acceptance (score 4.85).